Meningkatkan Penalaran Kritis Materi Gereja Sebagai Umat Allah Melalui Model PBL Fase F SMK PL Tarcisius Semarang - Alfonsus Agus Sulistiarso (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Times are always changing, so education should be carried out in accordance with the demands of these changes. If education is not adapted to changing times, the results will be outdated. Graduates will not be able to adapt. The Merdeka Curriculum is a concrete example of how change and innovation in education seeks to answer future challenges. In the context of the Independent Curriculum, Catholic religious and ethical education in Indonesia focuses on developing religious understanding, moral values ​​and Catholic spirituality for students. The Merdeka Curriculum emphasizes six Pancasila student profiles. And in this classroom action research, the researcher focuses on the dimensions of critical reasoning. The problem is that educators are accustomed to using the lecture method, so that students are less actively involved in the learning process. Based on the problem conditions above, educators can provide learning experiences by designing Problem Based Learning (PBL) learning models. The aim of the research is to find out how the use of the PBL model in improving critical reasoning on the material of the Church as the People of God and the nature of the One Church contributes to improving the learning outcomes of students in class XI AKL 1 SMK PL Tarcisius Semarang. The type of research used is qualitative with a descriptive approach.